2020
DOI: 10.3390/cells9061432
|View full text |Cite
|
Sign up to set email alerts
|

Symmetry Breaking and Emergence of Directional Flows in Minimal Actomyosin Cortices

Abstract: Cortical actomyosin flows, among other mechanisms, scale up spontaneous symmetry breaking and thus play pivotal roles in cell differentiation, division, and motility. According to many model systems, myosin motor-induced local contractions of initially isotropic actomyosin cortices are nucleation points for generating cortical flows. However, the positive feedback mechanisms by which spontaneous contractions can be amplified towards large-scale directed flows remain mostly speculative. To investigate such a pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…This is not surprising given that droplets could also not be deformed with cytoskeletal proteins due to their interfacial properties. [17,42] We thus moved to a compartment system which better mimics the mechanical properties of cellular membranes. We produced giant unilamellar lipid vesicles (GUVs) and functionalized them externally with the cholesteroltagged DNA (Figure 4c).…”
Section: Ph-induced Morphology Changementioning
confidence: 99%
“…This is not surprising given that droplets could also not be deformed with cytoskeletal proteins due to their interfacial properties. [17,42] We thus moved to a compartment system which better mimics the mechanical properties of cellular membranes. We produced giant unilamellar lipid vesicles (GUVs) and functionalized them externally with the cholesteroltagged DNA (Figure 4c).…”
Section: Ph-induced Morphology Changementioning
confidence: 99%
“…Encapsulated full cytoplasmic extracts are able to generate assembly, disassembly, and contraction of actomyosin networks 8 , 12 , 13 . The inclusion of motor proteins (as well as ATP production and oxygen scavenging) is key to achieve contraction and directed motion 14 . These advances point to exciting opportunities toward harnessing native cytoskeletal systems in synthetic cells.…”
Section: Introductionmentioning
confidence: 99%
“…Although open biomimetic platforms such as supported lipid bilayers, lipid-coated beads, and surface of GUVs introduce appropriate boundary conditions for self-assembly of cytoskeletal components into biochemically and mechanically functional networks 14,15,16,17,18,19 , they do not impose and demonstrate the influence of confined environment of the cell on network organization. To this end, protein components have been encapsulated within or attached to inside lipid-coated single emulsion droplets or GUVs 20,21,22,23,24 . Encapsulated microtubule-kinesin networks in droplets, for instance, reorganized into ring-like, cortical, or star-like structures based on droplet size 25,26 .…”
Section: Introductionmentioning
confidence: 99%
“…Although biomimetic platforms such as supported lipid bilayers [19][20][21] and the surfaces of giant unilamellar vesicles (GUVs) [22][23][24] introduce appropriate boundary conditions for selfassembly of actin network components into biochemically and mechanically functional networks, they do not confine components in the way that a cell does. To address this issue, actin cytoskeletal components have been encapsulated within or attached to the interiors of lipid-coated single emulsion droplets [25][26][27] or GUVs [27][28][29][30] . Studies that reconstitute actin and microtubule networks from purified components have revealed that spatial confinement can change the structures formed [31][32][33][34] .…”
Section: Introductionmentioning
confidence: 99%